2020
DOI: 10.1371/journal.pone.0232591
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1 (STC-1), a downstream effector molecule in latanoprost signaling, acts independent of the FP receptor for intraocular pressure reduction

Abstract: Prostaglandin F2 alpha (PGF2α) analogues such as latanoprost are common first-line intraocular pressure (IOP) lowering medications. However, their clinical use is limited in some patient populations due to minimal or no IOP lowering response or side effects. In searching for a more targeted approach for IOP reduction, our lab recently identified Stanniocalcin-1 (STC-1) as a molecule that was required for latanoprost-mediated IOP reduction and also acted as a stand-alone IOP lowering agent. In order to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…The ability of latanoprost to lower IOP depends on its binding to the FP receptor and activation of downstream signaling cascades [ 45 ]. We had previously shown that STC-1 was necessary for latanoprost-mediated IOP reduction [ 38 ] and when applied topically as an eye drop, could lower IOP through an FP receptor independent mechanism [ 39 ] To determine whether sustained IOP reduction following ssAAV2-STC-1-FLAG injection also did not require the FP receptor, we performed intracameral injections of ssAAV2-STC-1-FLAG in one eye and ssAAV2-GFP in the fellow eye of FP receptor knockout mice previously generated by our laboratory [ 28 ]. There was no difference in baseline IOP measurements between fellow eyes (16.3 ± 0.8 vs 16.3 ± 0.9 mmHg, n = 6, P = 0.8, Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability of latanoprost to lower IOP depends on its binding to the FP receptor and activation of downstream signaling cascades [ 45 ]. We had previously shown that STC-1 was necessary for latanoprost-mediated IOP reduction [ 38 ] and when applied topically as an eye drop, could lower IOP through an FP receptor independent mechanism [ 39 ] To determine whether sustained IOP reduction following ssAAV2-STC-1-FLAG injection also did not require the FP receptor, we performed intracameral injections of ssAAV2-STC-1-FLAG in one eye and ssAAV2-GFP in the fellow eye of FP receptor knockout mice previously generated by our laboratory [ 28 ]. There was no difference in baseline IOP measurements between fellow eyes (16.3 ± 0.8 vs 16.3 ± 0.9 mmHg, n = 6, P = 0.8, Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Three-month-old C57BL/6J wild-type or FP receptor knockout mice previously generated by our laboratory [ 39 ] were anesthetized with an intraperitoneal injection of ketamine/xylazine/acepromazine (80/6/1 mg/kg body weight) for intracameral injections. Mice were subsequently placed on a dissecting microscope to visualize the anterior chamber.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations